Nonlinear control of an induction motor taking into account saturation and rotor resistance variation effects - Mustapha Es-Semyhy; Abdellfattah Ba-Razzouk; Mustapha El Haroussi; Mhamed Madark (Institute of Advanced Engineering and Science, 2023)
Nowadays, electrical drives require more and more precision and reliability. Induction machine is one of the most robust actuators in terms of maintenance and reliability. Their control requires a good knowledge of the physical phenomena governing its operation. Saturation and heating are two main phenomena that must be taken into account to achieve the desired performance. In this paper, we will synthesize a nonlinear control law based on the “Backstepping” method, to regulate rotor speed and flux. This law takes into account saturation and rotor resistance variation effects. The immunity of the control to temperature rise will be tested. This control strategy is studied by simulation in the MATLAB/Simulink environment.